The Universals of Games and Sports - Parlebas, Pierre (Frontiers in Psychology, 2020)
We call "universals" the laws of order, the underlying objective systems on top of which are built the praxic exchanges that can be observed in all games and in all sports: operational models which represent the basic structures of the functioning of any sporting game and bearers of the fundamental features of its internal logic. Our objective is to test the differential influence of some of the possible forms of the universal of motor interactions from educational and cultural points o view. On the pedagogical level, the account is clear: the universality of communications generates relationships specific to each game, creating new contacts and opening up a field favourable to new attractions. we can only understand the alchemy of the relationships between players by taking into account the mechanisms of the development of the motor interactions of the universal.The numerical results recorded during these games reveal important phenomena, but they cannot be generalized in their detail: they serve to detect the most revealing points and to guide future research. Basically, they reveal the crucial role of the universal of motor interactions in the development of sports games and its effects on the conducts of players, regardless of their individual characteristics.On the cultural level, traditional games are the fruit of a history that has shaped their structures according to the values and collective representations of each region. The analysis of universals reveals that the alleged superior complexity of sports is an illusion. Quite on the contrary, what is evident is the remarkable simplicity of symmetrical duels and races, in contrast to the lush palette of the original structures of traditional games. Issued from the rules of the games, universals represent different social frameworks that call for individual motor action according to more or less permissive action logics. Taking them into account makes it possible to link the carefully collected, empirical materials to a reflection on the foundations of ludic conducts and, above all, on the foundations of motor action in general. Sporting games represent a specific world rich in psychological and sociological elements which calls out for in-depth scientific research.